2013
DOI: 10.1186/2049-2618-1-18
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in intestinal Clostridiales precede the development of nosocomial Clostridium difficile infection

Abstract: BackgroundAntimicrobial use is thought to suppress the intestinal microbiota, thereby impairing colonization resistance and allowing Clostridium difficile to infect the gut. Additional risk factors such as proton-pump inhibitors may also alter the intestinal microbiota and predispose patients to Clostridium difficile infection (CDI). This comparative metagenomic study investigates the relationship between epidemiologic exposures, intestinal bacterial populations and subsequent development of CDI in hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 36 publications
10
80
2
1
Order By: Relevance
“…Other investigations have shown that reduced alpha diversity is a reliable indicator of disease-associated dysbiosis [1,5456], corroborating our results. In relation to beta diversity, it was not possible to clearly distinguish individuals with distinct clinical status based on the composition of the gut microbiota.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other investigations have shown that reduced alpha diversity is a reliable indicator of disease-associated dysbiosis [1,5456], corroborating our results. In relation to beta diversity, it was not possible to clearly distinguish individuals with distinct clinical status based on the composition of the gut microbiota.…”
Section: Discussionsupporting
confidence: 92%
“…Koren et al [56] brought up also the possibility of a link between oral and intestinal microbiota with inflammatory diseases by investigating whether the oral or gut microbiota could contribute to atherosclerosis. They reported that several OTUs from oral and gut sources were also detected in atherosclerotic plaque within the same patients.…”
Section: Discussionmentioning
confidence: 99%
“…For mice, we previously demonstrated that the recovery of bacteria from the families Lachnospiraceae and Ruminococcaceae (phylum Firmicutes, order Clostridiales) corresponded directly with the timing of the recovery of in vivo resistance to colonization with VRE and C. difficile (23). For hospitalized patients, a reduction in the abundance of members of the order Clostridiales was independently associated with an increased risk of nosocomial CDI (24).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have demonstrated decreased intestinal microbial diversity among patients with rCDI compared to those with only one episode of CDI that does not recur [33], and diversity is reduced in patients with primary or rCDI compared to those with asymptomatic colonization [33,37,38]. Other studies have shown lower proportions of the family Clostridiales Incertae Sedis XI in patients who developed CDI compared to those who did not [39][40][41]. This deviation in the gut microbiota is thought to contribute to the loss of colonization resistance to C. difficile, as seen in animal and in vitro studies [42].…”
Section: Recurrent C Difficile Infection (Rcdi)mentioning
confidence: 99%